1999
DOI: 10.1515/bc.1999.021
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Signal Recognition and Elongation Arrest Activities of the Signal Recognition Particle

Abstract: The signal recognition particle (SRP), a ubiquitous cytoplasmic ribonucleoprotein particle, plays an essential role in promoting co-translational translocation of proteins into the endoplasmic reticulum. Here, we summarise recent progress made in the understanding of two essential SRP functions: the signal recognition function, which ensures the specificity, and the elongation arrest function, which increases the efficiency of translocation. Our discussion is based on functional data as well as on atomic struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…Taken together with our results, then, it seems very possible that only after SRP RNA-SRP19 assembly has occurred in the nucleolus does SRP54 subsequently bind elsewhere in the cell, either in the nucleoplasm or in the cytoplasm. SRP54 is unique among the SRP proteins in other ways: it can bind to signal sequences even without being complexed into the SRP (44)(45)(46) and it is the homologue to the only SRP protein known in E. coli, Ffh (45,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together with our results, then, it seems very possible that only after SRP RNA-SRP19 assembly has occurred in the nucleolus does SRP54 subsequently bind elsewhere in the cell, either in the nucleoplasm or in the cytoplasm. SRP54 is unique among the SRP proteins in other ways: it can bind to signal sequences even without being complexed into the SRP (44)(45)(46) and it is the homologue to the only SRP protein known in E. coli, Ffh (45,47).…”
Section: Discussionmentioning
confidence: 99%
“…For example, partially assembled SRPs may piggyback with ribosomal subunits for export from the nucleus. In this connection, it is worth noting that the SRP has a demonstrable affinity for ribosomes independent of its interaction with the nascent polypeptide signal sequence (9,45,49).…”
Section: Discussionmentioning
confidence: 99%
“…The mutational analysis and the atomic structure of murine SRP9/14 revealed regions or amino acid residues that are important in binding Alu RNA (Birse et al+, 1997;Bui et al+, 1997; for review, see Bui & Strub, 1999)+ These regions include the first a-helix and the adjacent loop in SRP9 and a flexible loop between b1 and b2 strands in SRP14+ In the heterodimer, these two regions lie in close proximity+ Furthermore, SRP9 and SRP14 form together a six-stranded b-sheet that is curved to fit duplex RNA and which is strongly positively charged, suggesting that the b-sheet may directly contact the RNA+ Many of these basic residues are conserved in evolution and the biochemical analysis of mutagenized proteins is consistent with a role for a subset of these residues in RNA-binding: arginine 59 in SRP14 as well as arginine 32 and lysine 41 in SRP9+ However, because of a simultaneous negative effect on dimerization, the role of these residues in RNA binding has not yet been established unequivocally (Bui et al+, 1997)+ Srp14p can be aligned with mammalian and plant SRP14 proteins based on sequence homology and on the conservation of structurally important residues (Birse et al+, 1997; Fig+ 5A)+ To examine whether the RNAbinding function has been conserved between the murine and the yeast SRP14 proteins, we produced mutagenized Srp14p proteins+ The RNA-binding capacities of the mutated proteins were analyzed as described above using biotinylated RNAs+ The dimerization functions of the altered proteins were analyzed by crosslinking and immunoprecipitation experiments+ Crosslinking was done as described before except that the in vitro-synthesized mutated Srp14p proteins were first partially purified on heparin beads+ We found that this procedure removes a large fraction of wheat germ components that give rise to nonspecific cross-linked products+ In the immunoprecipitation experiments, PhySrp14p was added cotranslationally to the translation reactions of the different Srp14p proteins+ Immobilized T7 Tag-specific antibodies were then used to assay formation of a homodimeric complex between the recombinant and the mutagenized protein+ We generated two mutated proteins in which two adjacent basic residues located before and in the middle of the putative loop region in Srp14p were changed into alanine and serine+ These residues include lysine 35 and arginine 36 as well as lysines 61 and 62 (14p35A/ 36S, 14p61A/62S; asterisks in Fig+ 5A)+ Both mutated proteins had a reduced RNA-binding capacity (Fig+ 5B)+ Replacing lysine 35 and arginine 36 completely abrogated the RNA-binding function, whereas changing lysines 61 and 62 reduced it by 50% as compared to Srp14p+ Neither protein bound to Alu RNA and the control RNA, confirming that the specificity in RNA recognition was unchanged+ In addition, the mutations interfered exclusively with the RNA-binding functions of the proteins, leaving their dimerization functions intact as shown with cross-linking and the immunoprecipitation experiments (Figs+ 5C and 5D)+ Cross-linked products of a comparable size were observed with the wild-type as well as with the mutated proteins, which migrated as expected of a homodimeric complex+ In addition, we had established in an experiment shown in Figure 2 that the cross-linked product is not the result of a fortuitous interaction of Srp14p with a wheat germ component+ The cross-linking efficiencies cannot be compared quantitatively in these experiments because the ratio of labeled to wheat germ proteins (which also get cross-linked) is not constant+ The transl...…”
Section: Srp14p Binds As a Homodimeric Complex To Scr1 Rnamentioning
confidence: 99%
“…The mammalian SRP has been used as a model for the extensive characterization of SRP functions+ It comprises six proteins and one RNA molecule (SRP or 7SL RNA)+ The SRP 54 protein specifically recognizes signal sequences and together with stem VIII of 7SL RNA is required for the targeting of the nascent chainribosome complex to the ER membrane (for review, see Lütcke, 1995)+ SRP54 and stem VIII of 7SL RNA represent the evolutionarily most highly conserved SRP structures and have been recognized in many organisms of all three kingdoms (for references, see Samuelsson & Zwieb, 1999)+ The 59 and 39 sequences of 7SL RNA that are homologous to the Alu family of repetitive sequences as well as two proteins, SRP9 and SRP14, constitute the Alu domain of mammalian SRP+ The Alu domain mediates a transient arrest in the elongation of nascent chains that increases the efficiency of translocation in vitro (Siegel & Walter, 1985;Thomas et al+, 1997; for a review, see Bui & Strub, 1999)+ SRP9 and SRP14 are structural homologs and members of the family of small a/b RNA-binding proteins (Birse et al+, 1997)+ Binding of SR9/14 to the Alu portion of 7SL RNA appears to induce conformational changes in the protein as well as in the RNA moieties (Janiak et al+, 1992;Bui et al+, 1997;Weichenrieder et al+, 1997)+ Such adaptive changes have been suggested to play a crucial role in the direct interaction between the Alu domain and the ribosome that affects elongation arrest (Thomas et al+, 1997)+…”
Section: Introductionmentioning
confidence: 99%
“…Protein targeting to the endoplasmic reticulum (ER) in eukaryotes and cell membrane in prokaryotes is catalyzed by the evolutionarily conserved signal recognition particle (SRP; Bui and Strub 1999;Keenan et al 2001). SRP binds ribosomes and nascent hydrophobic signal sequences at the N terminus of proteins destined for secretion or membrane integration.…”
Section: Introductionmentioning
confidence: 99%